Let's get rid of the cube roots. That will make the equations much easier to solve. To do this, we can cube both sides of the equation, as shown below:
Now, we can easily solve the equation.
The equation has a solution of x = -2.
Hey there!!
∛x - 5 = ∛ 4x + 1
Cube on both sides
x - 5 = 4x + 1
Add 5 on both sides
... x = 4x + 6
Subtract 4x on both sides
... -3x = 6
Divide by -3 on both sides
... x = 6 / -3
... x = -2
Hence, the final answer is -2.
Hope my answer helps!!
6.5m questions
8.6m answers